2021
DOI: 10.1038/s41386-020-00948-6
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation therapy with minocycline in treatment-resistant depression patients with low-grade peripheral inflammation: results from a double-blind randomised clinical trial

Abstract: This study aimed to investigate the role of baseline levels of peripheral inflammation when testing the efficacy of antidepressant augmentation with minocycline in patients with treatment-resistant depression. We conducted a 4-week, placebo-controlled, randomised clinical trial of minocycline (200 mg/day) added to antidepressant treatment in 39 patients selected for elevated levels of serum C-reactive protein (CRP ≥ 1 mg/L), n = 18 randomised to minocycline (M) and n = 21 to placebo (P). The main outcome was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 52 publications
2
122
3
Order By: Relevance
“…Recent literature highlights the crucial role of brain immune cells in depression pathology and any modality that can modulate the activity of these cells or reduce neuroinflammation, thereby bearing the potential to treat depressive symptoms. Supporting this notion, beneficial effects of anti-inflammatory drugs have been observed in MDD patients (Muller et al, 2006;Abbasi et al, 2012;Kobayashi et al, 2013;Majd et al, 2015;Cao et al, 2020;Nettis et al, 2021). Clinical trials using non-steroidal anti-inflammatory drugs in depressed patients have reported promising results, with increased remission rates in patients when used in combination with conventional antidepressant drugs (Abbasi et al, 2012;Cao et al, 2020).…”
Section: Targeting Microglia and Neuroinflammation In Depressionmentioning
confidence: 97%
See 3 more Smart Citations
“…Recent literature highlights the crucial role of brain immune cells in depression pathology and any modality that can modulate the activity of these cells or reduce neuroinflammation, thereby bearing the potential to treat depressive symptoms. Supporting this notion, beneficial effects of anti-inflammatory drugs have been observed in MDD patients (Muller et al, 2006;Abbasi et al, 2012;Kobayashi et al, 2013;Majd et al, 2015;Cao et al, 2020;Nettis et al, 2021). Clinical trials using non-steroidal anti-inflammatory drugs in depressed patients have reported promising results, with increased remission rates in patients when used in combination with conventional antidepressant drugs (Abbasi et al, 2012;Cao et al, 2020).…”
Section: Targeting Microglia and Neuroinflammation In Depressionmentioning
confidence: 97%
“…Yet, these models have provided useful insights into the neuroinflammatory mechanism of depression. Given that the role of neuroinflammation in human depression is yet not clear, the results of in vivo depression studies appear to be missing pieces of the puzzle of depression pathology (Nettis et al, 2021).…”
Section: Findings In Human Depression Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, in the same diseases or disease models, more targeted treatments focused on discrete or downstream inflammatory processes and effector cells have shown more promise. For example, in a double-blind randomized clinical trial with treatment resistant depression patients, found augmentation of minocycline (a tetracycline antibacterial) to anti-depressants improved behavioral symptoms in patients with low grade inflammation [ 31 ]. A meta-analysis also found minocycline to have significant anti-depressant activity and several clinical trials aimed to improve depression outcomes and improve treatment response scores in mood disorders with minocycline are currently underway [ 32 , 33 ].…”
Section: Neuroinflammationmentioning
confidence: 99%